Naturalness preserving image recoloring method for people with red–green deficiency - Hassan, M.F.; Paramesran, Raveendran (Elsevier, 2017)
People with red–green color vision deficiency may experience difficulties in discriminating colors. To enhance the visual details and improve their color perception, several recoloring methods have been considered. However, most of the recoloring methods take into consideration only the needs of red–green deficients, which may look unnatural to normal viewers or trichromats. This paper proposes a simple and efficient recoloring method that not only improves visual details and enhances the color perception of the red–green deficients but also preserves the naturalness of the recolored images for both trichromats and red–green deficients. Objective and subjective evaluations are conducted to evaluate the performance of the proposed method and three other recoloring methods. Results show that the proposed method performs better in terms of naturalness preservation and overall preference by trichromats and red–green deficients.